The “Christmas Effect” on defensive accelerated stocks - Meyni Christy Kuada; Setiani Mamonto (Yayasan Widyantara Nawasena Raharja, 2023)
The Christmas event in December 2022 is accompanied by an increase in inflation and also an increase in interest rates. The objective of this study is to examine the Christmas effect on optimal returns for investors. To analyze this phenomenon, this study carries out several stages, which are testing the market efficiency and estimating whether there are abnormal returns or not throughout the Christmas period. The consumer non-cyclical sector stocks in the accelerating trading board are used as the sample. The observation period is from 28 November 2022 to 20 January 2023 and is divided into two sub-periods. This study finds that market condition is inefficient before the Christmas event, resulting in higher abnormal returns and risks.